Mathematics Modeling of Diabetes Mellitus Type SEIIT By Considering Treatment And Genetic Factors - Asmaidi Asmaidi; Eka Dodi Suryanto (Jurnal Inotera, 2018)
SEIIT stands for Susceptible (S), Exposed (E), Infected population untreated (I) and Infected population treated (IT). Infected groups consisted in two categories, untreated (I) and with treatment (IT) by presented to insulin. Susceptible shifted to exposed by gene. Prefered outcomes are mathematical models for diabetes mellitus type SEIIT, conventional type, determining breakpoint and basic reproduction number, breakpoint analysis, breakpoint stability simulation. The results were mathematical models or diabetes mellitus compartment charts/diagrams. These diagram were both analysed analitically and numerically. The analyses presented two fixed points, with desease and without desease. Each point was analysed by its basic reproduction number, analitically and numerically, at fixed points without desease Ro < 1, while the other Ro > 1. Human population at condition Ro < 1 tent to move from susceptibel from the initial standpoint and becomes stabilized at . Proportion of exposed (e) is diminishing from the starting point and stabilized at e = 0. Infected untreated dimished from the initial stage and stabilized at i = 0 . Infected with treatment (iT) was increased from initial point, diminished and stabilized at iT = 0. Human behavior when R0 > 1, susceptible (s) increased at the beginning then fluctuated, stabilized finally at . Exposed (e) lower at first then stabilized at . Untreated infected group (i) lower from initial then stabilized when .00393. Treatment group initiate an increasing value, then fluctuated and stabilized at .